Implementasi Surat Edaran Nomor 15 Tahun 2020 Tentang Pedoman Penyelenggaraan Belajar dari Rumah dalam Masa Darurat Penyebaran Corona Virus Disease (Covid-19) di Sekolah Dasar Negeri Kabupaten Pati - Halimah, Halimah; Suyitno, Suyitno; Wijayanti, Arfilia (STKIP Andi Matappa Pangkep, 2021)
The purpose of this research is to know the implementation of circular no. 15 2020 about the guidelines for the implementation of the BDR in the period of the emergency the spread of COVID-19 SDN in Kawedanan Jakenan Pati Regency. This type of research is qualitative research using the approach of naturalistic. Methods of data analysis used is the analysis model of Miles and Huberman with the analysis of qualitative data are conducted interactively and takes place continuously. The results of the analysis of the implementation of the circular on guidelines for the implementation of BDR period of the emergency the spread of COVID-19 SDN in Kawedanan Jakenan, the show has done well and achieve 89,9%. It is examined through the 8 aspects, namely model management, learning systems, lesson plans, coaching and monitoring, advice and infrastructure, a parenting program, a team of emergency preparedness, and reports. The results obtained through the questionnaire with 72 respondents SDN, and interviews on the supervisory SDN. Feasibility BDR during the pandemic COVID-19 has run in accordance with the circular letter that applies. Overall aspects examined the head of SDN has been carrying out a circular letter.